Effectiveness of Modified Strength Training Using Rubber Bands In Improving the Speed of Dollyo Chagi Kick - Annafi'u Zahra Rihhadatul Aisy; Drastiana Siwi Maheswari (Universitas Negeri Semarang, 2026)
Dollyo chagi is one of the most commonly used techniques in taekwondo competitions that require physical ability, specifically speed. This study aims to determine the impact and effectiveness of modified strength training using rubber resistance bands on improving the speed of the dollyo chagi kick among taekwondo athletes at the RTA Academy Dojang in Kendal Regency. This study employed an experimental method using a one-group pretest-posttest design. The study sample consisted of 20 athletes aged 12–17 years, selected using purposive sampling. The research instrument used a 10-second dollyo chagi kicking speed test, measured in the number of kicks. The intervention was administered over 16 sessions, with a frequency of four times per week. Data analysis involved tests of normality, homogeneity, and hypothesis testing using a paired-sample t-test via the SPSS programme. The results of the study indicate that the data are normally distributed and homogeneous. The mean pretest score of 16.50 increased to 20.50 in the posttest. The results of the paired sample t-test showed a calculated t-value of -24.658 with a significance level of 0.000 (p < 0.05), indicating a significant difference between the pre-test and post-test results. It can therefore be concluded that training using modified rubber tyre resistance bands has a significant and effective impact on improving the speed of the dollyo chagi kick in taekwondo athletes.